Contextualizing Islamic Law in Resolving Customary Land Conflicts: A Siyasah Syar’iyyah Approach to the Semende Tribe’s Dispute in Bukit Barisan Selatan National Park - Imam Mahdi; Etry Mike; Arini Azka Mutia (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
This study aims to find a resolution to the forest ownership conflict between the Semende Tribe and the government in the Bukit Barisan Selatan National Park area. The conflict arose from the government's claim over the Dusun Lame Banding Agung region in Kaur Regency, Bengkulu Province, which was incorporated into the Bukit Barisan Selatan National Park (TNBBS), resulting in losses for the Semende Tribe, whose ancestral lands are located in this area. With the establishment of TNBBS, the Semende Tribe was displaced from their ancestral land. The conflict resolution needs to adopt the Siyasah Syar’iyyah approach to ensure social justice based on a win-win solution for all parties. This study employs a Normative-Empirical Legal Research method that is exploratory and descriptive in nature. Based on the study’s findings, conflict resolution can be achieved through a collaborative approach grounded in the principles of Siyasah Syar’iyyah, which prioritizes utility, humanity, and justice over mere legal certainty. This is proposed through a social forestry management concept. Social forestry becomes an alternative if the release of the forest area is difficult to realize. At the very least, the Semende Tribe can continue to utilize their fields and paddies in Dusun Lame Banding Agung as before, although not under customary land rights or customary forests, but through community-based forest management schemes. The contribution of this study lies in: (1) integrating the Siyasah Syar’iyyah framework with agrarian and forestry policies to formulate a more humane conflict resolution model; (2) proposing concrete policy mechanisms such as zoning revision and social forestry as realistic legal solutions; and (3) strengthening the protection of indigenous communities through a maqāṣid al-syarī‘ah perspective in conflict resolution within conservation areas